Organic and mineralogic heterogeneity of the Paris meteorite followed by FTIR hyperspectral imaging. (31st July 2018) - Dionnet, Z.; Aleon‐Toppani, A.; Baklouti, D.; Borondics, F.; Brisset, F.; Djouadi, Z.; Sandt, C.; Brunetto, R.
Abstract: Significant compositional and structural heterogeneity at nm to mm scales is an important characteristic of primitive extraterrestrial materials. Here, we report the analysis of high‐resolution Fourier transform IR hyperspectral imaging analytical measurements at the micron scale on a fragment of the Paris carbonaceous chondrite, supported by Raman and SEM‐EDS measurements. The fragment is crushed in a diamond compression cell. The micro‐FTIR analyses are performed in transmission with two setups, an imaging microscope with a matrix detector using a thermal source and a system using a single point detector coupled with the synchrotron source at the SOLEIL synchrotron facility. We obtain the spatial distribution of chemical/mineralogical components. We confirm at a larger scale (10 μm) the presence of hydrated amorphous silicates observed at a smaller scale (1 μm). Based on the relative abundance of different minerals (hydrated amorphous silicate, olivine, diopside, and serpentine), we propose a sequence of aqueous alteration. Considering the spatial correlation of minerals with organic matter, we discuss the effects of aqueous alteration on the organic matter in bulk. In particular, we detect an increase in the CH2 /CH3 ratio in the altered zone and present the possible scenarios that led to the observed chain length shortening/cracking of hydrocarbons.